2007
DOI: 10.1007/s10661-007-9743-x
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus fractions and adsorption characteristics of floodplain sediments in the lower reaches of the Hanjiang River, China

Abstract: The phosphorus fractions and adsorption characteristics of seven floodplain sediment samples collected in the lower reaches of China's Hanjiang River were studied. Most phosphorus fractions showed a marked downstream increase in response to point-source inputs from urban areas. Total phosphorus (TP) contents in the sediments ranged from 603.68 to 945.25 mg x kg(-1). Inorganic phosphorus (IP) was the major component of TP, and calcium-bound phosphorus (Ca-P) was the major fraction of IP. The distribution charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…On the other hand, in Varano lagoon, the results showed that as the proportion of fine particles increased, the amount of total phosphorus also increased, above all in response to point-source inputs (south-eastern side of the lagoon), indicating that fine particles had a stronger adsorption capacity for phosphorus and play an important role in determining the phosphorus content in sediments. Similar results have been also observed by other recent studies (Tian and Zhou 2008;Lukawska-Matuszewska and Bolalek 2008;Owens and Walling 2002;Selig 2003;Vermont et al 2002). On the basis of these observations (highlighted by PCA analysis also), a not marked but evident difference between the two lagoons was observed and supported by ANOSIM test that suggested a greater influence of external sources on sediment macronutrient distributions in Varano rather than in Lesina lagoon.…”
Section: Discussionsupporting
confidence: 90%
“…On the other hand, in Varano lagoon, the results showed that as the proportion of fine particles increased, the amount of total phosphorus also increased, above all in response to point-source inputs (south-eastern side of the lagoon), indicating that fine particles had a stronger adsorption capacity for phosphorus and play an important role in determining the phosphorus content in sediments. Similar results have been also observed by other recent studies (Tian and Zhou 2008;Lukawska-Matuszewska and Bolalek 2008;Owens and Walling 2002;Selig 2003;Vermont et al 2002). On the basis of these observations (highlighted by PCA analysis also), a not marked but evident difference between the two lagoons was observed and supported by ANOSIM test that suggested a greater influence of external sources on sediment macronutrient distributions in Varano rather than in Lesina lagoon.…”
Section: Discussionsupporting
confidence: 90%
“…In Swan Lake, TP concentrations in surface sediments were not high, ranging at 79–616 mg/kg, which were similar to the margin sediments in Yellow Sea , but lower than other estuarine and coastal sediments of China, such as the wetland of Yellow River Delta , and the estuarine sediments of Daliao River . The spatial distribution of sediment P is mainly related to anthropogenic inputs, sediment texture, hydrodynamic conditions, and the distribution of aquatic organisms . In Swan Lake, highest TP concentrations were observed at the NW corner and central area, the lowest at SE corner.…”
Section: Discussionmentioning
confidence: 86%
“…P sorption on the sediments is an important process that affects P transport between the sediments and overlying water. P sorption characteristics mainly depend on sediment composition, such as amorphous Fe and Al , organic matter (OM) , grain size , and carbonate . However, the dominant factor influencing P adsorption was different in various aquatic systems.…”
Section: Introductionmentioning
confidence: 99%
“…The published studies on the ecological environment related to this project have mainly focused on the area upstream of the Danjiangkou Dam, and there have been fewer studies on the middle and lower reaches ( Li et al, 2012 ). Published studies on the middle and lower reaches of the Hanjiang River have mainly focused on ecohydrological conditions, sediment regimes, characteristics of floodplain sediments, diatom blooms and other phenomena related to the changes in physical environment ( Tian and Zhou, 2008 ; Lu et al, 2012 ; Yang Q. et al, 2012 ; Wang et al, 2015 ). Compared to a single dam, the impact of cascade hydropower dam construction on watershed ecosystems is more serious owing to its multiple instances of obstruction and interception ( Rodríguez-Pérez et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%